2022
DOI: 10.1097/phm.0000000000002122
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Early Inpatient Rehabilitation of Post COVID 19 Survivors-Single Center Retrospective Analysis

Abstract: The aim of this study was to understand the demographic, clinical characteristics, and effectiveness of early inpatient rehabilitation of post-COVID survivors. Design: A single-center retrospective chart review analysis of 100 patients admitted to a newly created acute COVID rehabilitation unit (CORE+) from April to December 2020 was conducted. Results: The demographic and clinical characteristics and complications of 100 post-COVID patients were reviewed. Functional outcomes of GG Self-care and Mobility Activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Studies have shown that COVID-19 patients make significant gains during inpatient rehabilitation. 102 This is true even for patients who have the most severe illness at the time of admission to rehabilitation. 103 Rehabilitation hospitals and systems experienced substantial strain during the heights of the COVID-19 pandemic.…”
Section: Recommendations To Promote Neurologic Recovery After Covid-19mentioning
confidence: 99%
“…Studies have shown that COVID-19 patients make significant gains during inpatient rehabilitation. 102 This is true even for patients who have the most severe illness at the time of admission to rehabilitation. 103 Rehabilitation hospitals and systems experienced substantial strain during the heights of the COVID-19 pandemic.…”
Section: Recommendations To Promote Neurologic Recovery After Covid-19mentioning
confidence: 99%